The Effect of Applying the Hypnolearning Model on Motivation and Biology Learning Outcomes of Students at SMA Negeri 1 Pekanbaru - Al Khudri Sembiring; Rahmat Ramadansur; Marta Dinata (SEARCH: Science Education Research Journal, 2026)
Learning motivation and biology learning outcomes are important factors that determine students' success in the learning process. However, many senior high school students still experience low learning motivation, poor concentration, and unsatisfactory learning outcomes due to the predominance of conventional teaching methods. Therefore, innovative learning models are needed to create a more engaging and effective learning environment. This study aimed to determine the effect of the Hypnolearning model on students’ learning motivation and biology learning outcomes at SMA Negeri 1 Pekanbaru. The study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of two classes selected through purposive sampling, namely an experimental class taught using the Hypnolearning model and a control class taught using conventional learning methods. Data were collected through learning motivation questionnaires and biology achievement tests and were analyzed using an independent sample t-test. The results indicated that the implementation of the Hypnolearning model had a positive effect on students’ learning motivation and biology learning outcomes, as evidenced by higher motivation scores and improved learning outcomes in the experimental class compared to the control class. In conclusion, the Hypnolearning model can serve as an effective alternative learning approach to enhance students’ motivation and biology learning outcomes while creating a more enjoyable and conducive learning atmosphere.